Limits to host colonization and speciation in a radiation of parasitic finches. (9th March 2021) - Jamie, Gabriel A; Hamama, Silky; Moya, Collins; Kilner, Rebecca M; Spottiswoode, Claire N
Abstract: Parasite lineages vary widely in species richness. In some clades, speciation is linked to the colonization of new hosts. This is the case in the indigobirds and whydahs ( Vidua ), brood-parasitic finches whose nestlings mimic the phenotypes of their specific hosts. To understand the factors limiting host colonization and, therefore, speciation, we simulated the colonization of a host using cross-fostering experiments in the field. Despite DNA barcoding suggesting that host species feed their chicks similar diets, nestling Vidua had low survival in their new host environment. Nestling Vidua did not alter their begging calls plastically to match those of the new hosts and were fed less compared to both host chicks and to Vidua chicks in their natural host nests. This suggests that a key hurdle in colonizing new hosts is obtaining the right amount rather than the right type of food from host parents. This highlights the importance of mimetic nestling phenotypes in soliciting feeding from foster parents and may explain why successful colonizations tend to be of hosts closely related to the ancestral one. That nonmimetic chicks are fed less but not actively rejected by host parents suggests how selection from hosts can be sufficiently intense to cause parasite adaptation, yet sufficiently relaxed that parasitic chicks can sometimes survive in and colonize new host environments even if they lack accurate mimetic phenotypes. The difficulties of soliciting sufficient food from novel foster parents, together with habitat filters, likely limit the colonization of new hosts and, therefore, speciation in this parasite radiation. Abstract : Why are some groups species rich, while others are species poor? For Africa's brood-parasitic finches, species richness is intimately tied to the colonization of new host species. Using field experiments, we show that a major obstacle to host switching and, therefore, speciating is obtaining the right amount of food from the new host parent rather than the right type of food. This is possible when parasite and host chicks have similar nestling begging displays.